DARI ONDERAFDEELING HINGGA TERBENTUKNYA KABUPATEN JENEPONTO (1909-1959) - Ismail Syawal (Moderasi: Jurnal Studi Ilmu Pengetahuan Sosial, 2023)
This study focuses on Jeneponto as a Regency in South Sulawesi Province. In the historiography of South Sulawesi, Jeneponto has not been written much, including its changes since becoming Onderaffdeling until its formation as a Regency. This change prompted the writer to examine the occurrence of these changes, especially the transition from Onderafdeeling to the current Jeneponto Regency. This study uses the historical method through four stages, namely Heuristics, Criticism, Interpretation, and Historiography. The results of this study found three things, namely: (1) the Turatea Kingdom appeared as one of the Makassar kingdoms in Jeneponto which formed a unity called the Turatea Confederation (Toeratea-anden). This confederation was formed from three karaeng-an regions, namely Binamu, Bangkala, and Laikang; (2) When Turatea was annexed by the Dutch East Indies, in 1909 the Dutch East Indies government carried out a regional arrangement. One form of arrangement is the establishment of Onderafdeeling Jeneponto; and (3) Jeneponto was formed as a Level II Region/Regency in 1959 based on Law number 29 of 1959. The issuance of the Law was based on regional conditions, both in terms of population and security. The growth and development of Jeneponto Regency is inseparable from its history, economy, politics, and socio-culture.